Extending the mass “backbone” to short-lived nuclides with ISOLTRAP - Guénaut, Celine; Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
New measurements performed with the Penning trap mass spectrometer ISOLTRAP extend the backbone to short-lived species. Recently obtained mass results are presented.
Gesehen am 03.03.2020